Assessment of Good Manufacturing Practices (GMP) in Selected Food Industries of Bangladesh (Bangladesh Journal of Nutrition, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/bjnut.v22i0.12828 Bangladesh Journal of Nutrition Vol.22-23 2009-2010 pp.21-29